MASYARAKAT UTILITARIAN, AGAMA, DAN KEHIDUPAN EKONOMI - Riyardi, Agung (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2004)
Utilitarianism community utilizes individual sovereignty as the most preferable factor to promote economic. Religion(s) is one of others, when individual sovereignty can not promote economic. But to promote economic, religion(s) has to appropriate with individual sovereignty. From this view, Adam Smith argues religions and not one religion in the community to promote economic. Unfortunately it can come to conclude that religion(s) does not exist in the utilitarianism community.